Potential use of tree species in a secondary forest in Lages, Santa Catarina (Revista de Ciências Agroveterinárias, 2012)
This study aimed at quantifying and listing the species potentially useful in a secondary forest in the municipality of Lages, SC. The study was carried out in a forest fragment using 25 plots of 400 m2 allocated in a systematic stratified way. All trees with DBH (diameter at breast height) ≥ 5 cm were measured and identifi ed. In addition, the species that were not sampled in the plots were identified during random walks in the fragment in order to complement the floristic list. The species potential usage was obtained by means of bibliographic consultation and personal observations. Eighty-seven species distributed into 36 botanic families were found. The species with the highest number of individuals were Araucaria angustifolia (Bert.) Kuntze (198), for several applications, such as timber and food, and Myrcia splendens (Sw.) DC. (159), which can be potentially used in urban arborization and in the restoration of degraded lands. The results showed that the secondary forest fragment has species with potential for timber (31%) and non timber use (69%).
Keywords: Araucaria forest; Mixed Ombrophilous Forest; Floristic.